2022
DOI: 10.1111/bjc.12380
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal, social support, and parental burnout

Abstract: Objectives: Parental burnout is a prevalent condition that affects parents' functioning and health. While various protective factors have been examined, little is known about their interplay. In the current study, we examined the joint effect of two protective factors against parental burnout

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…Only one study explored the consequences of PB and how ER buffered those effects (Yang et al, 2021). As expected, results showed that cognitive reappraisal acted as a protective factor of PB, directly (Swit & Breen, 2023) or by buffering the effects of lack of social support (Lin et al, 2022) and COVID-parental stress (Vertsberger et al, 2022). It seems that cognitive reappraisal by changing the meaning attributed to events and, consequently, the emotions experienced, contributed to dealing with parenting demands even in the presence of other constraints such as lack of social support and COVID-related stress.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Only one study explored the consequences of PB and how ER buffered those effects (Yang et al, 2021). As expected, results showed that cognitive reappraisal acted as a protective factor of PB, directly (Swit & Breen, 2023) or by buffering the effects of lack of social support (Lin et al, 2022) and COVID-parental stress (Vertsberger et al, 2022). It seems that cognitive reappraisal by changing the meaning attributed to events and, consequently, the emotions experienced, contributed to dealing with parenting demands even in the presence of other constraints such as lack of social support and COVID-related stress.…”
Section: Discussionmentioning
confidence: 88%
“…Expressive suppression did not moderate the effect of PB on parenting practices and adolescents' mental health, nor the effect of lack of social support (Lin et al, 2022;Yang et al, 2021). However, it explained the link between perfectionism and PB (Lin et al, 2022). Probably because expressive suppression occurs late in the emotion-generative process and relates to inhibition of expressive behavior (Gross & Levenson, 1997), it may have more direct effects on individuals' functioning and do not contribute to buffer or exacerbate the effects of other psychosocial variables.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations